Asymmetric Two‐Component Alkenyl Catellani Reaction for the Construction of C—N Axial Chirality - Wu, Chenggui; Liu, Ze‐Shui; Shang, Yong; Liu, Chang; Deng, Shuang; Cheng, Hong‐Gang; Cong, Hengjiang; Jiao, Yinchun; Zhou, Qianghui (Chinese journal of chemistry, 2024)
Comprehensive Summary Herein, we report an asymmetric two‐component alkenyl Catellani reaction for the construction of C—N axial chirality through a palladium/chiral norbornene cooperative catalysis and an axial‐to‐axial chirality transfer process. Various partially aromatic iodinated 2‐pyridones, quinolones, coumarin and uracil substrates react with 2,6‐disubstituted aryl bromides with a tethered amide group, to afford a wide variety of polycyclic C—N atropisomers (38 examples, up to 97% e.e.). The obtained C—N axial chirality originates from the preformed transient C—C axial chirality with high fidelity. The synthetic utility of this chemistry is demonstrated by facile preparation of complex quinoline and pyridine based C—N atropisomers through a N‐deprotection and aromatization sequence. In addition, a remote axial‐to‐central diastereoinduction process dictated by C—N axial chirality is observed with excellent diastereocontrol. An asymmetric two‐component alkenyl Catellani reaction for the construction of C—N axial chirality is reported. This method is based on a palladium/chiral norbornene cooperative catalysis and an axial‐to‐axial chirality transfer process.